2022
DOI: 10.3390/pathogens11101194
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiological Investigation of Piroplasms and Anaplasmataceae Bacteria in Egyptian Domestic Animals and Associated Ticks

Abstract: Piroplasmosis and anaplasmosis are serious tick-borne diseases (TBDs) that are concerning for the public and animal health. This study aimed to detect the molecular prevalence and epidemiological risk factors of Piroplasma and Anaplasma species in animal hosts and their associated ticks in Egypt. A total of 234 blood samples and 95 adult ticks were collected from animal hosts (112 cattle, 38 sheep, 28 goats, 26 buffaloes, 22 donkeys, and 8 horses) from six provinces of Egypt (AL-Faiyum, AL-Giza, Beni-Suef, Al-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
(128 reference statements)
1
1
1
Order By: Relevance
“…Regarding sex as a studied individual variable factor, this study found that the overall prevalence of blood parasites in male sheep was significantly higher compared to females, which aligns with earlier studies conducted nationally or internationally ( 63 – 66 ). However, the present findings are in contrast with another reports in Egypt ( 31 , 33 , 62 ). This variation may stem from a notable difference in the sample size of males and females included in our study which could influence the prevalence rates ( 67 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Regarding sex as a studied individual variable factor, this study found that the overall prevalence of blood parasites in male sheep was significantly higher compared to females, which aligns with earlier studies conducted nationally or internationally ( 63 – 66 ). However, the present findings are in contrast with another reports in Egypt ( 31 , 33 , 62 ). This variation may stem from a notable difference in the sample size of males and females included in our study which could influence the prevalence rates ( 67 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, Elsayed et al ( 33 ) in North Coast of Egypt concluded that the infection with blood parasites was higher in sheep more than 3 years. Another study ( 62 ) in Egypt recorded a higher infection rate in animals aged ≤ 1 year. The discrepancies observed between the current findings and other studies could be attributed to variations in sanitary and hygienic practices, the number of examined animals, variations in immunological resistance, and the impact of local climatic conditions, which may influence the spread of ticks ( 32 ).…”
Section: Discussionmentioning
confidence: 93%
“…The Babesiosis is one of the most important local diseases of the blood parasitic and tick born disease in Iraq and especially Basrah governorate as explained in the previous studies such as (Sawitri1 et al 2021 ., Moayad andHasso , 2019) this may be due to the tropical or semi tropical in Basrah as mentioned by (Vikrant Sudan et al 2013& Olaa et al 2017 due to the high temperature and wet weather moreover this weather will help the tick infestation which regard as the main source of babesiosis., this agree with (Alsaad et al 2016& Sobhy et al 2022 The clinical signs which include the fever is due to the immunity reaction as we know and explained by (Sawitri et al 2021& Jasim et al 2023, in the other hand the anorexia and inappitance which lead to the loss of the body weight then emaciation and low milk production while the jaundice mucous membrane in fact result in due to the anemia which caused by the B. bigemina that cause severe decrease in the red blood corpuscles due to the damage of it then leading to hemoglobinuria that affect the kidney function this results agree with (Olaa et al 2017, Sawitri et al 2021& Mohammed et al 2020.…”
Section: Discussionsupporting
confidence: 86%